2022
DOI: 10.2147/idr.s360945
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Escherichia coli and Klebsiella pneumoniae Strains Resistant to the Oxyimino-Cephalosporins and the Monobactam by Production of GES Type Extended Spectrum Bêta-Lactamase (ESBL) at Saint Camille Hospital Center in Ouagadougou, Burkina Faso

Abstract: Background: Bacterial resistance to beta lactamins is a real public health problem as it complicates treatment strategies. Several types of beta lactamase confer this resistance. Numerous studies report a high prevalence of ESBL producers among Gram-negative bacilli. The objective of this work was to identify the presence of the resistance gene GES in strains of E. coli and K. pneumoniae in Burkina Faso. Methods: During this study 39 strains of E. coli and K. pneumoniae resistant to oxyimino-cephalosporin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…With respect to the significant association found in the present study between the aztreonam resistance phenotype and the presence of the bla GES gene in E. coli, this also supports the recent worldwide report of bla GES as a carbapenemase harbored by K. pneumoniae, E. coli, and P. aeruginosa [39][40][41]. Mehrotra et al (2023) [12] also previously described bla CTX-M-15 , bla CMY-42 , bla NDM-5 , and aadA(2) as prevalent in E. coli, and we have also detected a high presence of bla PSE in these isolates.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the significant association found in the present study between the aztreonam resistance phenotype and the presence of the bla GES gene in E. coli, this also supports the recent worldwide report of bla GES as a carbapenemase harbored by K. pneumoniae, E. coli, and P. aeruginosa [39][40][41]. Mehrotra et al (2023) [12] also previously described bla CTX-M-15 , bla CMY-42 , bla NDM-5 , and aadA(2) as prevalent in E. coli, and we have also detected a high presence of bla PSE in these isolates.…”
Section: Discussionsupporting
confidence: 91%
“…This fact could be explained by the existence of other resistance mechanisms in our isolates, such as the production of ESBLs or other carbapenemases and defects in cell wall permeability. Indeed, in a previous study conducted in 2022 by Tiemtore et al (2022) in Burkina Faso, blaGES gene encoding Guiana Extended-Spectrum (GES) carbapenemase has been detected in Imipenem-resistant enterobacteriaceae strains included in this study. Thus, eventual presence of GES-2 variant, exhibiting an increased hydrolysis of carbapenems (Poirel et al, 2001), in our bacterial strains, might justified carbapenem resistance of IMP gene-negative isolates.…”
Section: Discussionmentioning
confidence: 69%
“…In Africa, IMP enzymes had been in Egypt (Masoud et al, 2021;Benmahmod et al, 2019;Abbas et al, 2019), Morocco (Barguigua et al, 2013), Tunisia (Chouchani et al, 2011;Dziri et al, 2020), Tanzania (Mushi et al, 2014) and Sudan (Adam and Elhag, 2018). In Burkina Faso, most of the studies were much focused on ESBLproducing Enterobacteriaceae which occurs resistant to beta-lactam (Metuor Dabire et al, 2013;Metuor et al, 2019a;Metuor Dabire et al, 2019b;Tiemtore et al, 2022) at the expense of carbapenemases, mainly MBL despite the threat they represent for heath care. Nevertheless, previous studies (Sanou et al, 2020;Dembele et al, 2021;Kabore et al, 2022Kabore et al, , 2023 have reported resistance to carbapenems in GNB by the production of carbapenemases.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates were identi ed using routine phenotypic and biochemical tests. The con rmed isolates were preserved in trypticase soy broth (Merck Co., Darmstadt, Germany) containing 20% glycerol and stored at − 70°C until used [9].…”
Section: Methodsmentioning
confidence: 99%